Pemenuhan Hak Normatif Buruh Harian Lepas Pada PT. Hanuraba Sawit Kencana - Layang Sardana; Suryati Suryati (Universitas Batanghari Jambi, 2020)
Type of this research was normative legal research that were descriptive and supported by data as for the packaging in this study is: Is there a gap in the fulfillment of the normative rights of freelance workers under Law No. 13 of 2003 on Employment and Ministerial Decree No. 100 of 2004 on the Terms of Certain Time Employment Agreements with practice at PT. Hanuraba Sawit Kencana? Based on the results of research that has been done in PT. HanurabaSawitKencana, can be summed up some things about the form of labor agreement between freelance labors and PT. HanurabaSawitKencana and the responsibilities of PT. HanuarabaSawitKencana towards the fulfillment of normative rights of freelance labors has been carried out in accordance with Law No. 13 of 2003 on Employment and Ministerial Decision No. 100 of 2004 On The Tenaity of The Implementation of Certain Time Work Agreements.